Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s12282-015-0623-x
|View full text |Cite
|
Sign up to set email alerts
|

Pertuzumab, trastuzumab and docetaxel reduced the recurrence of brain metastasis from breast cancer: a case report

Abstract: The CLEOPATRA trial reported the survival benefit of pertuzumab with trastuzumab plus docetaxel in HER2-positive metastatic breast cancer patients. However, there are a few case reports concerning the effects of a pertuzumab-containing regimen on brain metastases. A 55-year-old woman, who underwent curative surgery for breast cancer after neoadjuvant chemotherapy 5 years previously, developed repeated solitary brain metastasis in her right occipital lobe. Whole brain radiation therapy, stereotactic radiosurger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“… 1 Despite advances in treatment methods, such as surgery, chemotherapy, radiation therapy, and biological therapy, the percentage of death in BC patients remains high. Although targeted therapies using antibodies, such as pertuzumab and trastuzumab, have significantly improved the treatment of BC in recent years, 2 4 some investigations reported that 30%–70% of BC patients relapse after 5 years. 5 …”
Section: Introductionmentioning
confidence: 99%
“… 1 Despite advances in treatment methods, such as surgery, chemotherapy, radiation therapy, and biological therapy, the percentage of death in BC patients remains high. Although targeted therapies using antibodies, such as pertuzumab and trastuzumab, have significantly improved the treatment of BC in recent years, 2 4 some investigations reported that 30%–70% of BC patients relapse after 5 years. 5 …”
Section: Introductionmentioning
confidence: 99%
“…Patients like ours are usually not involved in clinical trials due to their poor performance status that is allegedly related to bad prognosis, and the optimal therapy remains an open question. Until today, only one case with brain metastases has been reported to experience complete response under second-line combination of pertuzumab-trastuzumab and docetaxel [ 20 ]. A retrospective study including patients rechallenged with trastuzumab after second-line lapatinib therapy for CNS involvement indicated a rather poor median OS of 17.3 (3.4–32.2) months [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“… 76 Furthermore, in a case report, pertuzumab with trastuzumab plus docetaxel was effective in reducing the recurrence of BCBM in a patient who was heavily pretreated. 77 Based on these findings, further trials are warranted to investigate the effect of this regimen among patients with HER2-positive BCBM.…”
Section: Targeted Therapy For Her2-positive Bcbmmentioning
confidence: 99%